ANALISIS TERHADAP KEBUTUHAN DESAIN PEMBELAJARAN MATEMATIKA BERBASIS PERMAINAN DI SEKOLAH MENENGAH PERTAMA - Pertiwi, Nazmi Gita; Wahyuni, Windi; Kosasih, Usep; Saputra, Samnur (Uninus Journal of Mathematics Education and Science (UJMES), 2023)
This study aims to analyze the needs of mathematics learning designs for educators and students at the junior high school (SMP) level. The research method used was descriptive qualitative with the research subjects being junior high school mathematics educators and seventh grade students. The research instruments used were interview sheets and questionnaire sheets. The results of the study show that there are still many students who are constrained and have difficulty understanding online mathematics learning. Then educators also still lack variety in interesting learning media for students, so they don't get bored and are passionate about learning mathematics. The conclusion from this study is that the design of mathematics learning at the junior high school level is still in the less category because there are still many students who have difficulty learning and understanding mathematics and there are still many educators who do not yet have an attractive learning design and increase the enthusiasm for learning for students, so a design is needed. game-based learning. The benefits of this research can be used as a preliminary study to conduct further research on junior high school mathematics learning design.